Steps to co-develop agro-climatic bulletin (ACB) for local agricultural planning and decision-making - Alliance of Bioversity International and CIAT; Ministry of Agriculture and Rural Development, Vietnam; Southern Regional Hydro-Meteorological Centre, Vietnam; Ninh Thuan Hydro-Meteorological Centre, Vietnam (DeRISK SE Asia, 2022)
This guidebook is about managing climate risks and provides a step-by-step manual for the development of climate-informed agricultural advisories or Agro-Climatic Bulletin (ACB). It is based on experiences of a pilot in the Mekong River Delta (MRD) and South-Central Coast (SCC) by the Alliance Bioversity & CIAT with the Department of Crop Production of the Ministry of Agriculture and Rural Development (MARD-DCP), and local partners in MRD and SCC. Alongside capacity building materials for training sessions, the manual aims to support the implementation and scaling of ACBs to other districts and provinces in the MRD and SSC and other regions in the country.